Muscarinic receptor signaling in the amygdala is required for conditioned taste aversion. (1st January 2021) - Morin, Jean-Pascal; Rodríguez-Nava, Emmanuel; Torres-García, Víctor Manuel; Contreras-Vázquez, Omar Alejandro; Castellanos-Pérez, César Armando; Tovar-Díaz, Jorge; Roldán-Roldán, Gabriel
Highlights: Pre-conditioning blocking of muscarinic receptors in the BLA or the CeA impairs both short and long-term memory of conditioned taste aversion. Post-conditioning blocking of muscarinic receptors in the CeA or the BLA has no effect on conditioned taste aversion short or long-term memory. Blocking of muscarinic receptors in the BLA, but not in the CeA before long-term memory test attenuates conditioned taste aversion retrieval. Abstract: The sense of taste provides information regarding the nutrient content, safety or potential toxicity of an edible. This is accomplished via a combination of innate and learned taste preferences. In conditioned taste aversion (CTA), rats learn to avoid ingesting a taste that has previously been paired with gastric malaise. Recent evidence points to a role of cholinergic muscarinic signaling in the amygdala for the learning and storage of emotional memories. The present study tested the participation of muscarinic receptors in the amygdala during the formation of CTA by infusing the non-specific antagonist scopolamine into the basolateral or central subnuclei before or after conditioning, as well as before retrieval. Our data show that regardless of the site of infusion, pre-conditioning administration of scopolamine impaired CTA acquisition whereas post-conditioning infusion did not affect its storage. Also, infusions into the basolateral but not in the central amygdala before retrieval test partially reduced the expression of CTA. Our results indicate that muscarinic receptors activity is required for acquisition but not consolidation of CTA. In addition, our data add to recent evidence pointing to a role of cholinergic signaling in peri-hippocampal structures in the process of memory retrieval.